Telithromycin and Quinupristin-Dalfopristin Induce Delayed Death in Plasmodium falciparum - Barthel, Diana (American Society for Microbiology (ASM), 2008)
Antibacterial agents are used in malaria therapy due to their effect on two prokaryote organelles, the mitochondrion and the apicoplast. We demonstrate here that the ribosome-blocking antibiotics telithromycin and quinupristin-dalfopristin, but not linezolid, inhibit the growth of Plasmodium falciparum. Both drugs induce delayed death in the parasite, suggesting that their effect involves the impairment of apicoplast translation processes.